RANCANG BANGUN PENGELOLAAN LAB BERBASIS FIREBASE CLOUD MESSAGING DAN MOTION DETECTION CAMERA MENGGUNAKAN RASPBERRY PI - Arsito Ari Kuncoro; Edy Noriyanto; Febryantahanuji Febryantahanuji (STEKOM PRESS, 2019)
Security aspects is needed in various fields of life today. Safety is becoming a concern for everyone. One of the important concerns is the security of the room. The indoor security system uses Raspberry Pi and RFID based Firebase Cloud Messaging and Motion Detection Camera, is a room security system that includes expensive equipment, so this device is designed for protection or robbery and also provides assistance in advance. . The security system in this room consists of several parts, namely Raspberry Pi as a brain system, selenoid door lock as an electric lock on the door, RFID system and CCTV camera as a detector of the amount of human movement, PIR sensor as a detector of human temperature, alarm as an indicator of intruders which transfers rooms, and database applications as user storage databases for security recorders